2002
DOI: 10.1530/eje.0.1460505
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone substitution of hypogonadal men prevents the age-dependent increases in body mass index, body fat and leptin seen in healthy ageing men: results of a cross-sectional study

Abstract: Introduction: In healthy men, body weight and total fat content increase with advancing age, while serum testosterone levels decrease. In order to elucidate whether a causal relationship between these phenomena exists, we investigated the influence of testosterone or human chorionic gonadotrophin substitution on body mass index (BMI), total fat mass and serum leptin in testosterone-treated and untreated hypogonadal patients in comparison with ageing eugonadal men. Methods: In a cross-sectional study, the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 42 publications
1
24
1
8
Order By: Relevance
“…In contrast, an association between the CAG repeat length and the percentage of body fat has been reported by others (8,9). The latter is at odds with the linear relationship reported by Crabbe et al between CAG number and free testosterone (25), since higher levels of testosterone are usually associated with lower adiposity (26,27). Our study showed a direct association between the length of CAG repeats and free testosterone levels, which may in part explain the lower fat accumulation in CAG L compared to CAG S .…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, an association between the CAG repeat length and the percentage of body fat has been reported by others (8,9). The latter is at odds with the linear relationship reported by Crabbe et al between CAG number and free testosterone (25), since higher levels of testosterone are usually associated with lower adiposity (26,27). Our study showed a direct association between the length of CAG repeats and free testosterone levels, which may in part explain the lower fat accumulation in CAG L compared to CAG S .…”
Section: Discussionmentioning
confidence: 93%
“…The importance of adequate serum testosterone levels for acquisition and maintenance of bone and muscle mass has been generally accepted and body compositional changes in men under testosterone treatment have been described by several studies (10,45,46). For CF patients no associations between serum testosterone levels and LBM or weight were observed, whereas only a weak but significant relationship was found for testosterone and BMD.…”
Section: Discussionmentioning
confidence: 99%
“…TRT causes an increase in lean body mass in younger men, 38,39 in middle-aged men, 40,41 and in aging men. 42 The effect of TRT on adipose tissue has been somewhat less consistent, probably because of differences in body fat.…”
Section: Testosterone Treatment Of Testosteronedeficient Menmentioning
confidence: 99%